Key organizational and HR factors for rapid technology assimilation - Kontoghiorghes, Constantine (My University, 2005)
This study attempted to prioritize key organizational factors that effected technology assimilation in two information technology units of a large automaker. Frequent introduction and use of technology in quality efforts as well as a risk-taking and innovation-driven culture were found to be the strongest predictors of rapid technology assimilation.